Immunomodulatory Role of the Extracellular Matrix Within the Liver Disease Microenvironment - McQuitty, Claire E.; Williams, Roger; Chokshi, Shilpa; Urbani, Luca (Frontiers in Immunology, 2020)
Chronic liver disease when accompanied by underlying fibrosis, is characterised by an accumulation of extracellular matrix (ECM) proteins and chronic inflammation. Although traditionally considered as a passive and largely architectural structure, the ECM is now being recognised as a source of potent DAMPs with immune-active peptides and domains. In parallel, the ECM anchors a range of cytokines, chemokines and growth factors, all of which are capable of modulating the immune responses. A growing body of evidence shows that ECM proteins themselves are capable of interacting both directly, via a wide range of receptors including integrins and TLRs, and indirectly with immune cells. ECM deposition and remodelling during fibrosis can result in release or formation of ECM-DAMPs, which can drive immune cellular infiltration and sterile inflammation. Both the ECM and immune response are interlinked and integral in driving fibrosis, although their precise interactions in the context of chronic liver disease are poorly understood. This review aims to shed light on the ECM-immune interactions underlying liver disease, in particular fibrosis of different aetiologies, by describing the main ECM intact proteins and ECM-DAMPs with known immune regulatory activity. We also discuss how tissue engineering could provide new opportunities to explore ECM-immune cell interactions in bioreactor-based dynamic 3D models containing intact decellularized ECM scaffolds. A better understanding of these interactions would aid in the identification of new antifibrotic and immunomodulatory targets for treatment and biomarkers in liver disease.